Clinical effectiveness in severe knee osteoarthritis after intra-articular platelet-rich plasma in association with hyaluronic acid injection: three case reports - Chen SH (Dove Medical Press, 2016)
Szu-Hsuan Chen,1,* Ta-Shen Kuan,2,3,* Mu-Jung Kao,4 Wei-Ting Wu,1 Li-Wei Chou1,5 1Department of Physical Medicine and Rehabilitation, China Medical University Hospital, Taichung, 2Department of Physical Medicine and Rehabilitation, College of Medicine, 3Department of Physical Medicine and Rehabilitation, National Cheng Kung University Hospital, College of Medicine, National Cheng Kung University, Tainan, 4Department of Rehabilitation, Taipei City Hospital, Zhong Xiao Branch, Taipei, 5Graduate Institute of Acupuncture Science, College of Chinese Medicine, China Medical University, Taichung, Taiwan, Republic of China *These authors contributed equally to this work Abstract: Osteoarthritis (OA) is a degenerative disorder resulting from loss of joint cartilage and underlying bone and causes pain and loss of function. The treatment of knee OA is still a challenge because of the poor self-regeneration capacity of cartilage. The nonsurgical interventions include control of the aggravating factor (such as weight control and the use of walking aids), symptomatic treatment (such as acetaminophen or nonsteroidal anti-inflammatory drugs), prolotherapy, and viscosupplementation. However, the combination of platelet-rich plasma (PRP) and hyaluronic acid (HA) has not been widely used because of lack of clinical evidence and several limitations in patients with severe knee OA. Three patients who suffered from knee pain and poor walking endurance were diagnosed with advanced knee OA. They underwent PRP treatment in association with intra-articular HA injection and showed pain relief and functional improvement. The follow-up standard weight-bearing X-ray images of knees also confirmed the improvement and indicated the possibility of regeneration of the articular cartilage. These cases provide clinical and radiographic evidence for a new therapy for advanced knee OA. This treatment strategy of PRP in association with HA injection can offer a chance to treat severe knee OA, rather than immediate surgery, or a chance for those who cannot undergo surgery. It can also postpone the need of arthroplasty and can significantly improve the daily activity function. Keywords: hyaluronic acid injection, knee osteoarthritis, platelet-rich plasma, regeneration, X-ray